Aplikasi Pengurusan Acara Perlumbaan Persatuan Berbasikal Pulau Pinang: Penang Cycling Association Racing Event Management Application - Hassan, Muhammad Aiman Haikal; Samsudin, Noor Azah (Applied Information Technology And Computer Science, 2022)
The Penang Cycling Association's Racing Event Management Application online was developed to make it easier for the organizers to manage all participant data and avoid any fraud the races carried out to replace the existing system manually. Most of the new entrants are not familiar with the roads that are new to them. Therefore, some participants are astray and some use the pitas road. In addition, the organizers have difficulty monitoring certain categories for each participant according to their year of birth. The management system of the cycling Association was developed to help the organizers track the participants' positions. This system can also be accessed anywhere because it is a mobile application-based system. With this system, the organizers can access the profile of participants to monitor the performance of participants either increased or decreased. Participants can know the position of the checkpoint easily. The system is also capable of displaying the final results for each event competed. This system was developed based on prototype model activities. It is hoped that this system can help to solve the issue.